2014
DOI: 10.1007/s00221-014-4100-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modulation of Cdk5 contributes to memory deficiency induced by amyloid fibrils

Abstract: Alzheimer's disease (AD) is a frequent neurodegenerative disorder with progressive neuroinflammation, loss of synaptic plasticity in central neurons and memory deficiency. Numerous studies demonstrated the epigenetic modification of the expression of specific genes involved in the pathogenesis of amyloid-associated memory deficiency. It was also reported that dysregulation of cyclin-dependent kinase 5 (Cdk5) activity critically contributed to the synaptic dysfunction and memory deficiency in the rodent model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Numerous studies have presented compelling evidence implicating Cdk5 in homeostatic synaptic formation and plasticity [76] (Fig. 2).…”
Section: Cdk5 Modulates Synaptic Plasticitymentioning
confidence: 99%
“…Numerous studies have presented compelling evidence implicating Cdk5 in homeostatic synaptic formation and plasticity [76] (Fig. 2).…”
Section: Cdk5 Modulates Synaptic Plasticitymentioning
confidence: 99%
“…These deficits were caused by an inability of TrkB receptors to be phosphorylated and interact with Rac1 for dendritic spine remodeling and reveals the importance of Cdk5 for LTP and spatial memory formation (86). Interestingly, abnormal Cdk5 activity has been implicated in AD pathology (100)(101)(102)(103).…”
Section: Potential Mediators Of Xbp1 Signaling In Neuronsmentioning
confidence: 99%
“…For example, one study found that glioblastoma cells which express 2.6-fold higher levels of APP display a global reduction DNA methylation and this hypomethylation resulted in the ectopic expression of several ADassociated genes such as PS1, BACE1 and APP itself [107]. In the rat model of AD, increased H3 acetylation and decreased promoter methylation in the region of cyclin dependant kinase 5 (cdk5), lead to increased hippocampal cdk5 activity, tau phosphorylation, synaptic dysfunction and memory loss [104].…”
Section: Epigenetic Changes In Age-related Diseasesmentioning
confidence: 99%
“…AD is a progressive neurodegenerative disorder that can occur in old age and is often characterized by accumulation of amyloid β peptides and abnormally phosphorylated tau proteins [104,105]. The altered methylation state of the AD brain typically results in gene expression alterations in two primary pathogenic pathways: amyloid precursor protein (APP) processing and tau hyper phosphorylation [102,106].…”
Section: Epigenetic Changes In Age-related Diseasesmentioning
confidence: 99%